Pengaruh Perbedaan Ketinggian Tempat Terhadap Capaian Hasil Inseminasi Buatan Pada Kambing Peranakan Ettawa - Setyo Utomo (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2013)
This study was conducted to assess the reproductive performance and achievements of AI in goat reared in lowland and highland areas. The study used a survey method in two rural areas with the highest goat population. For lowland areas selected Karangwuni village while highland areas was Sidomulyo village. The results showed that for the lowland areas vs. the highland for reproductive performance were as follows: age of first estrus (10 vs 9.3 bl), age of first mating (13.2 vs 12.5 bl),mating system 100% natural, post partum mating (4.2 vs 4.6 months), S / C (1.5 vs. 1.6). Understanding of farmers about the pregnant female: anestrus post-AI (85.7 vs. 22.2%), stomach down (14.3 vs. 0.00), the condition of the udder (0.00 vs 77.8%). Achievement results of AI (37.5 vs. 40%). Based on the results of the study concluded that the reproductive performance of goat in lowland areas was generally very similar to the highland areas, thus the development of large-scale goats in the lowland areas is recommended.Key words: natural mating, artificial insemination, PE goats, lowland, highland